CORPORA-ALLATA IN FEMALES OF NEOPONERA-VILLOSA ANTS (HYMENOPTERA FORMICIDAE) - RELATIONS WITH OVARIAN DEVELOPMENT - Mathias, Maria Izabel Camargo [UNESP]; Caetano, F. H. (California State University, 1995)
In female ants of the species Neoponera villosa the corpora allata are paired structures located dorsolaterally to the esophagus (Camargo-Mathias and Caetano, 1991). In the present study the glandular volume of the corpora allata was estimated and the activity of the glands was compared with the ovarian development. In the workers there was a relation between activity of these glands and ovaries in stages 0 to IV. In workers, with ovaries at stage V (maximum development) there was a smaller activity of the corpora allata. Another increasing activity was found in workers with ovaries at stage VII.In the queens, mainly those which were mated, whose ovaries were always fully developed, the volume of the corpora allata was smaller than those of the workers.